Diet and lifestyle factors associated with fish consumption in men and women: a study of whether gender differences can result in gender-specific confounding - Wennberg Maria; Tornevi Andreas; Johansson Ingegerd; Hörnell Agneta; Norberg Margareta; Bergdahl Ingvar A (Nutrition Journal, 2012)
Abstract Background Fish consumption and intake of omega-3 fatty acids from fish are associated with a lower risk of cardiovascular disease. However, a prospective study from northern Sweden showed that high consumption of fish is associated with an increased risk of stroke in men, but not in women. The current study aimed to determine if fish consumption is differently related to lifestyle in men compared with women in northern Sweden. Methods Lifestyle information on 32,782 men and 34,866 women (aged 30–60 years) was collected between 1992 and 2006 within the Västerbotten Intervention Programme (a health intervention in northern Sweden). Spearman correlations coefficients (R s ) were calculated between self-reported consumption of fish and other food items. Lifestyle variables were compared between fish consumption categories. Results Fish consumption was positively associated with other foods considered healthy (e.g., root vegetables, lettuce/cabbage/spinach/broccoli, chicken, and berries; R s = 0.21-0.30), as well as with other healthy lifestyle factors (e.g., exercise and not smoking) and a higher educational level, in both men and women. The only gender difference found, concerned the association between fish consumption and alcohol consumption. Men who were high consumers of fish had a higher intake of all types of alcohol compared with low to moderate fish consumers. For women, this was true only for wine. Conclusions Except for alcohol, the association between fish consumption and healthy lifestyle did not differ between men and women in northern Sweden. It is important to adjust for other lifestyle variables and socioeconomic variables in studies concerning the effect of fish consumption on disease outcome.